Evaluation of in ovo feeding of low or high mixtures of cysteine and lysine on performance, intestinal morphology and physiological responses of thermal-challenged broiler embryos - Ajayi, O. I.; Smith, O. F.; Oso, A. O.; Oke, O. E. (Frontiers in Physiology, 2022)
The objective of this study was to evaluate the effect of in ovo feeding cysteine, lysine or their combinations on the perinatal and post-hatch physiological responses of broiler embryos exposed to heat stress during incubation. A total of two thousand fertile eggs of broiler breeders (Ross 308) flock (at 38 weeks of age) were used for this study. In the first ten days, the eggs were incubated using the conventional protocol of relative humidity and temperature and 55% and 37.8ºC. From day ten onward, the temperature was increased to 39.6ºC. On day 17.5, 1500 eggs with the evidence of living embryos were randomly selected and assigned to 6 treatments having five replicates of 50 eggs each. The treatments were: un-injected eggs(UI), eggs injected with only 0.5mL distilled water(DW), 3.5mg/egg cysteine(CY), 2mg/egg lysine(LY), 3.4mg cysteine+2mg lysine(CLH) and 1.7mg cysteine+1mg lysine(CLL). On day 21, the hatchability, anatomical characteristics, chick quality and the antioxidant status of the chicks were evaluated. During the post-hatch phase, data were collected on the haematology, biochemical parameters, growth performance and intestinal morphology of the birds. The results revealed that the hatchability of CY chicks was higher (P< 0.05) than in the other treatments, while the lowest values were recorded in CLH. The hatching muscle of the chicks of CLL was similar to those of CY but higher (P<0.05) compared to the others. The MDA of DW and UI chickens was similar and higher than birds in the other treatment groups. The serum SOD of CLL birds was comparable to that of CY but higher than the values recorded in the other treatments. The final weights of CLL chickens were similar to those of LY but significantly higher (P<0.05) than those of the other treatments. The duodenal villus heights of the birds of CLL were higher than those of the other treatment groups, whereas the villus height of the birds of CLH was higher than those of UI, DW and CY. Overall, in ovo feeding of cysteine alone improved the hatchability of thermally-challenged broiler embryos. In contrast, a low-dose mixture of cysteine plus lysine improved the post-hatch growth performance.